Avifauna composition and richness in four vegetation types, San Ramón, Costa Rica (UNED Research Journal, 2019)
Introduction: wild birds are important for humans as biological control and seed dispersers, among others. In turn, they can be affected by changes in landscape structure. Objective: to analyze the composition and richness of avifauna in four vegetation types of San Ramón, Costa Rica, between May and August 2016. Methods: point sampling with a fixed 25m radius (75m between points, 10min per observation) produced 548 individuals from 27 families and 75 species. Results: the most abundant species were Ramphocelus passerinii, Turdus grayi, Crotophaga sulcirostris and Troglodytes aedon. Species richness and abundance were higher in pasture with high canopy cover, and in riverine forest, than in live fences and pastures with low canopy cover. Habitats with the most similarity were riverine forest and live fences. Additionally, 39% of the represented species were insectivorous, 23% frugivorous, 17% omnivorous, 16% carnivorous, 4% seed eaters, and 1% was nectar eater. Lastly, five species were “Forest Dependent” and six were “Indicative of Forest”. Conclusion: finally, it should be noted that the areas with the highest vegetation coverage, food availability and refuge areas were the ones with the highest number of species and the most similar sites are determined by the connectivity between them.
Keywords: habitats; riparian forest; live fences; abundance; richness